A multifaceted review on dihydromyricetin resources, extraction, bioavailability, biotransformation, bioactivities, and food applications with future perspectives to maximize its value. Issue 4 (17th December 2021) - Zhang, Haolin; Caprioli, Giovanni; Hussain, Hidayat; Le, Nguyen Phan Khoi; Farag, Mohamed A.; Xiao, Jianbo
Abstract : Natural bioactive compounds present a better alternative to prevent and treat chronic diseases owing to their lower toxicity and abundant resources. (+)‐Dihydromyricetin (DMY) is a flavanonol, possessing numerous interesting bioactivities with abundant resources. This review provides a comprehensive overview of the recent advances in DMY natural resources, stereoisomerism, physicochemical properties, extraction, biosynthesis, pharmacokinetics, and biotransformation. Stereoisomerism of DMY should be considered for better indication of its efficacy. Biotechnological approach presents a potential tool for the production of DMY using microbial cell factories. DMY high instability is related to its powerful antioxidant capacity due to pyrogallol moiety in ring B, and whether preparation of other analogues could demonstrate improved properties. DMY demonstrates poor bioavailability based on its low solubility and permeability with several attempts to improve its pharmacokinetics and efficacy. DMY possesses various pharmacological effects, which have been proven by many in vitro and in vivo experiments, while clinical trials are rather scarce, with underlying action mechanisms remaining unclear. Consequently, to maximize the usefulness of DMY in nutraceuticals, improvement in bioavailability, and better understanding of its actions mechanisms and drug interactions ought to be examined in the future along with more clinical evidence.